Defects in vertically vibrated monolayers of cylinders. (15th March 2019) - González-Pinto, Miguel; Renner, Johannes; de las Heras, Daniel; Martínez-Ratón, Yuri; Velasco, Enrique
Abstract: We analyse liquid-crystalline ordering in vertically vibrated monolayers of cylinders confined in a circular cavity. Short cylinders form tetratic arrangements with C4 symmetry. This symmetry, which is incompatible with the geometry of the cavity, is restored by the presence of four point defects with total topological charge +4. Equilibrium Monte Carlo simulations predict the same structure. A new method to measure the elastic properties of the tetratic medium is developed which exploits the clear similarities between the vibrated dissipative system and the thermal equilibrium system. Our observations open up a new avenue to investigate the formation of defects in response to boundary conditions, an issue which is very difficult to realise in colloidal or molecular systems.